Sin Stocks in Self Managed Superannuation Funds - Peter J. Phillips (Australasian Accounting, Business and Finance Journal, 2011)
Ethical or responsible investing has attracted much attention over the last decade. Financial planners can now advise clients on a broad range of ethical investment products and some financial planning firms have this as their sole activity. Interestingly, the alter ego of ethical investing, sin or vice investing, has attracted far less attention. Recent research shows that ‘sinful’ investments can generate very strong returns and should certainly not be avoided by investors without a full evaluation of the consequences of excluding these investments from the portfolio. This paper extends these findings into the field of self managed superannuation funds operating within an Australian context. The prevalence of sinful investments within a sample of SMSFs and the returns that may be generated by a portfolio consisting of sinful Australian equities is examined. Analysis reveals that the SMSF investors within the sample do not include very many sin stocks in their portfolios. However, it does not appear as though SMSF trustees are missing an important investment opportunity because the analysis reveals that an equally-weighted portfolio of all vice or sin shares is unlikely to generate superior returns.
Keywords: Self managed superannuation funds; SMSF; sin; vice; investing.